(untitled) (Pravaha, 2021)
The study aims to assess the public perception on the effectiveness of health insurance services provided by the Government of Nepal. This study adopts a descriptive and analytical research design. A sample of usable 135 respondents was collected using purposive sampling method from the respondents in Kathmandu District. The influencing factors of public perception taken were level of awareness, information sources, level of satisfaction and problems faced. The study also examined the public perception influenced on the health insurance service growth in Nepal. The study concluded that for the successful implementation of health insurance coverage, it was found necessary to understand the basic dynamics of consumer preferences, service providers, acceptability, and pricing of health insurance products.